Benralizumab treatment and 3-dimensional bronchial tree changes in chronic eosinophilic pneumonia - Yoshiro Kai, MD, PhD; Yuichi Hishida, RT (Journal of Allergy and Clinical Immunology: Global)
Patients with chronic eosinophilic pneumonia often experience recurring disease and prolonged corticosteroid use with adverse effects. Benralizumab enabled corticosteroid discontinuation and successfully treated chronic eosinophilic pneumonia in our study, confirmed through remission induction therapy and 3-dimensional bronchial tree visualization.